Analisis Pembangunan Ekonomi Melalui Pengembangan Potensi UMKM di Era Pandemi Covid 19 di Kota Medan - Sari Lubis, Nuh Aulya; Lubis, Nurul Rafiqoh; Alvira, Rivta; Hanifah, Shofiya; Wulandari, Sari (Jurnal Etnik: Ekonomi-Teknik, 2022)
Since the arrival of the Covid-19 phenomenon, it has changed people's consumption behavior a lot, at the beginning of the Covid-19 Pandemi it proved that the Covid-19 disaster greatly affected the health, social, tourism, and economic conditions of an area. Regions that basically rely on the most superior economic sector for regional progress, have finally been neglected due to the arrival of this virus. One of them is MSMEs, currently MSMEs are experiencing various problems such as declining sales, capital, hampered distribution, difficulty in raw materials, declining production and layoffs of workers, this is a threat to the national economy. This research focuses on the generation and development of MSMEs by utilizing digital technology into businesses and the government's efforts to facilitate MSMEs to grow the Indonesian economy during the Covid-19 Pandemi, which has existed since the beginning of 2019 and has had many negative impacts on the world's economic sector, including Indonesia. The data collection technique in this research is library research. The type of data used is secondary data in the form of books, journals, articles, brochures, and other data relevant to the research theme. The results of this study are how business actors use digital technology in making new product innovations and how the government revives the economic sector by facilitating MSMEs.